QoS routing algorithm based on multiple domain architecture of SDN - Wei HUANG; Ran LU; Cuncai LIU; Sibo QI (网络与信息安全学报)
Traditional distributed network architecture constraints the innovation of routing algorithm.Software-defined network (SDN) provides a new solution for the optimization of routing algorithm.Previous researches show that the quality of service (QoS) routing issues are based on heuristic algorithm mostly,but these methods cannot be applied in large networks due to their high computing complexity.However,other algorithms have a lot of problems,which are high complexity or poor QoS performance,such as shortest path algorithm.This paper proposes A new QoS routing algorithm:LC-LD routing algorithm was proposed.LC-LD was based on SDN west-east interface and binds both delay constraint and cost constraint.keeping a good balance between computational complexity and algorithm performance.Finally,the simulation results show that LC-LD can possess both low computational complexity and high QoS routing performance.